Heteronormative system justification and wellbeing among sexual minorities in Brazil: the role of internalized homophobia and in-group identification - Bruno Ponte Belarmino Lima; Luana Elayne de Cunha Souza; Tiago Jessé Souza de Lima (Frontiers in Social Psychology)
One of the major tenets of system-justification theory is that justifying the social system exerts a palliative effect, being associated with positive wellbeing outcomes. Findings regarding this effect on social minorities, however, are less clear. The present article aims to propose and test a model explaining how system-justification relates to the wellbeing of Brazilian lesbians, gays and bisexuals, integrating variables previously studied independently, such as internalized homophobia and in-group identification. Seven-hundred and seventy-seven Brazilian cisgender LGBs responded to an online questionnaire. A simple mediation analysis and a moderated mediation model were conducted through Macro Process for SPSS. As expected, system-justification is indirectly associated with negative wellbeing outcomes through the internalization of homophobia. This relationship, however, is moderated by sexual minority subgroups, so that the mediation is only significant for gay men. On the other hand, system-justification is directly related to positive wellbeing outcomes (supporting the palliative effect). This positive relationship, however, is moderated by in-group identification, so that the higher the identification, the weaker is the association. Results are critically discussed and the collective and long-term implications of system-justification and its palliative effect are addressed.